Tailoring nanowire lasing modes via coupling to metal gratings - Vitale, F.; Repp, D.; Siefke, T.; Zeitner, U.; Peschel, Ulf; Pertsch, Thomas; Ronning, Carsten (Applied Physics Letters, 2023)
Tailoring the emission of plasmonic nanowire-based lasers represents one of the major challenges in the field of nanoplasmonics, given the envisaged integration of such devices into on-chip all-optical circuits. In this study, we proposed a mode selection scheme based on distributed feedback, achieved via the external coupling of single zinc oxide nanowires to an aluminum grating, which enabled a quasi-single mode lasing action. The nano-manipulation of a single nanowire allowed for a reliable comparison of lasing emission characteristics in both planar (i.e., a nanowire on the metallic substrate) and on-grating configurations. We found that, by varying the orientation of the nanowire on the grating, only when the nano-cavity was perpendicular to the ridge direction, an additional peak emerged in the emission spectrum on the low-energy side of the gain envelope. As a consequence of the fulfillment of the Bragg condition, such a peak was attributed to a hybrid mode dominating the mode competition. Simulation results showed that the hybrid mode could be efficiently waveguided along the nanowire cavity and supported by localized plasmon polaritons building up at the raised features ("fences") on top of metal grating ridges. Moreover, the hybrid mode was found to experience an extra reflectance of nearly 50% across the grating periods in addition to that provided by nanowire end facets.
CRIS-Team Scopus Importer:2023-04-20